Analysis of Word Embeddings - Thurnbauer, Matthias Johannes (Jihočeská univerzita, 2023)
The influence of the window size on semantic and thematic similarities between words was analyzed for the algorithms Word2Vec and Glove. Furthermore, a disambiguation method was proposed using a density based clustering algorithm called DBSCAN. The report also contains performance measurements regarding the training times of these static word embedding algorithms showing the influence of the token normalization process.
Analysis of Word Embeddings
Keywords: Word Embeddings; DBSCAN; Cosine Similarity; Semantic; Thematic; Word2Vec; GloVe; Word Embeddings; DBSCAN; Cosine Similarity; Semantic; Thematic; Word2Vec; GloVe